Hubungan Kebiasaan Makan Sayur dan Buah saat Kehamilan dengan Kebiasaan Makan Sayur dan Buah pada Anak Usia Pra Sekolah di Desa Waode Buri Kecamatan Kulisusu Utara Kabupaten Buton Utara - Herianto, Herianto; Aru, Mirda (Jurnal Gizi Ilmiah, 2017)
Based on 2013 basic health research data, the proportion of eating less vegetables and fruits in Indonesia is very high, namely 93.6%. Riskesdas data for Southeast Sulawesi in 2013, states that almost the entire population aged 10 years and over does not consume vegetables and fruit. This study aims to determine the relationship between the habit of eating vegetables during pregnancy with the habit of eating vegetables and fruit in pre-school age children in the village of Waode Buri, North Kulisusu District, North Buton Regency. This type of research is analytical descriptive using a cross-sectional study approach. The research site is Waode Buri Village, North Kulisusu District, North Buton Regency. This research was conducted on 10 – 28 May 2017. The research population was 55 people. The sample in this study amounted to 55 people. The sampling technique used a saturated sample. Collecting data using a questionnaire. This study was analyzed using the chi square test. The results showed that there was a relationship between the habit of eating vegetables and fruit during pregnancy with the habit of eating vegetables and fruit in pre-school age children in the village of Waode Buri, North Kulisusu District, North Buton Regency, the value of a = 0.05 and the value of value = 0.01. The results of this study can be concluded that to start the habit of eating vegetables and fruit can be started during pregnancy. If the mother's habit of eating vegetables and fruit is good during pregnancy, it can be taught to children and if the child is accustomed to eating vegetables and fruit, it is hoped that the amount of consumption of vegetables and fruit for children will increase and have long-term health effects. .